2004
DOI: 10.1161/01.atv.0000134529.65173.08
|View full text |Cite
|
Sign up to set email alerts
|

Rat Aortic MCP-1 and Its Receptor CCR2 Increase With Age and Alter Vascular Smooth Muscle Cell Function

Abstract: Objective-With age, rat arterial walls thicken and vascular smooth muscle cells (VSMCs) exhibit enhanced migration and proliferation. Monocyte chemotactic protein-1 (MCP-1) affects these VSMC properties in vitro. Because arterial angiotensin II, which induces MCP-1 expression, increases with age, we hypothesized that aortic MCP-1 and its receptor CCR2 are also upregulated and affect VSMC properties. Methods and Results-Both MCP-1 and CCR2 mRNAs and proteins increased in old (30-month) versus young (8-month) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
176
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(196 citation statements)
references
References 67 publications
14
176
1
5
Order By: Relevance
“…In this context, we showed that these environmental conditions activate the transcription factor activator protein 1 (AP‐1), which controls expression of genes with products that promote cellular activity and proliferation in the venous wall. Among them, monocyte chemoattractant protein 1 (MCP1) contributes to the recruitment of circulating monocytes and proliferation of vascular smooth muscle cells (SMCs),5, 6 whereas matrix metalloproteinase (MMP) 2 promotes degradation and thus structural rearrangement of the extracellular matrix in the vessel wall 7, 8. Consequently, an increase in wall stress stimulates expression of MMP2 and elevates gelatinase activity in the media of affected veins and human venous SMCs (HUVSMCs) 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we showed that these environmental conditions activate the transcription factor activator protein 1 (AP‐1), which controls expression of genes with products that promote cellular activity and proliferation in the venous wall. Among them, monocyte chemoattractant protein 1 (MCP1) contributes to the recruitment of circulating monocytes and proliferation of vascular smooth muscle cells (SMCs),5, 6 whereas matrix metalloproteinase (MMP) 2 promotes degradation and thus structural rearrangement of the extracellular matrix in the vessel wall 7, 8. Consequently, an increase in wall stress stimulates expression of MMP2 and elevates gelatinase activity in the media of affected veins and human venous SMCs (HUVSMCs) 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…Immunoblotting of supernatant from thoracic aortae homogenates or VSMC lysates were performed as previously described 5, 6, 19, 20. Primary antibodies used for Western blotting are listed in Table.…”
Section: Methodsmentioning
confidence: 99%
“…VSMCs were enzymatically isolated as previously described 5, 6, 19, 20. Briefly, young and old AL and CR F344 rat thoracic aortae (n=3 animals/group) were rinsed in Hanks balanced salt solution containing 50 μg/mL penicillin, 50 μg/mL streptomycin, and 0.25 μg/mL amphotericin B (ThermoFisher).…”
Section: Methodsmentioning
confidence: 99%
“…SB202190 and the rabbit anti-fibronectin antibody were from Calbiochem (Nottingham, UK). The protein kinase C (PKC) peptide inhibitors PKC [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and SN50 were from Alexis (Nottingham, UK) and the TransAM nuclear factor kappa B (NF-κB) kit was from Active Motif (Rixensart, Belgium). The FITC-conjugated rabbit antimouse antibody, the rabbit anti-fibronectin antibody and the avidin/biotin blocking solution were from DAKOCytomation (Glostrup, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…Inhibition experiments on basal protein production were carried out simultaneously. RS102895 (6 μmol/l), anti-TGF-β1 neutralising antibody (2 μg/ml), SN50 (18 μmol/l), SB202190 (1 μmol/l) and PKC [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] (4 μmol/l) were used to block CCR2, TGF-β1, NF-κB, p38 mitogen-activated protein (MAP) kinase and PKC, respectively. The specificity and selectivity of the inhibitors used has been previously demonstrated [22][23][24][25].…”
Section: In Vitro Studymentioning
confidence: 99%